Extrapulmonary tuberculosis with renal and intestinal involvement: A challenge in early diagnosis (Research, Society and Development, 2023)
Extrapulmonary tuberculosis is a manifestation of lung disease that affects organs and systems other than the lungs. Its incidence has increased, especially in patients with immunosuppression. Diagnosis and treatment of this form of the disease are clinical challenges due to the diversity of affected organs. Symptoms vary depending on the affected location and accurate diagnosis requires a multidisciplinary approach. Brazil has a high burden of tuberculosis and the extrapulmonary form accounts for around 20% of reported cases. This study aims to present a recent case report of extrapulmonary tuberculosis with renal and intestinal involvement, analyzing the signs and symptoms manifested by the patient, the diagnostic approaches used and the treatment instituted based on the most up-to-date scientific evidence. A clinical case report methodology with descriptive qualitative characteristics was used, carried out at the Hospital located in the city of Taubaté/SP. The patient received appropriate treatment and had a satisfactory clinical and laboratory evolution, resulting in functional recovery. Currently, the patient continues to be monitored at the Municipal University Hospital of Taubaté, under the care of the Nephrology and Hepatology team.